Beneficial use of sediments to restore a Chesapeake Bay marsh island - Davis, Jenny; Whitfield, Paula; Giannelli, Ryan; Golden, Rebecca; Greene, Michael; Poussard, Leanne; Whitbeck, Matthew (Frontiers in Sustainability, 2024)
Despite rapidly expanding interest in the use of natural coastal habitats for their ability to protect against erosion and flooding, implementation of coastal natural infrastructure (NI) projects has been limited to date. Uncertainty over how the benefits of NI will change over time as they mature and adapt to changing environmental drivers, and a lack of well-documented demonstrations of NI, are often cited as roadblocks to their widespread acceptance. Here, we begin to fill that knowledge gap by describing implementation and early (3 years post-implementation) monitoring results of an NI project at Swan Island, MD. Swan is an uninhabited marsh island in mid-Chesapeake Bay, USA whose position renders it a natural wave break for the downwind town of Ewell, MD. Prior to project implementation, Swan had experienced significant losses in aerial extent due to subsidence and erosion. To reverse this trend, the island was amended with dredged sediments in the winter of 2018-2019. The overarching goal was to preserve the Island's ability to serve as a wave break and make it more resilient to future sea level rise by increasing the elevation of the vegetated platform, while also increasing the diversity of habitats present. A monitoring program was implemented immediately after sediment placement to document changes in the island footprint and topography over time and to evaluate the extent to which project goals are met. Data from the initial three years of this effort (2019 through 2022) indicate an island that is still actively evolving, and point to the need for rapid establishment of vegetative communities to ensure success of coastal NI.